1988
DOI: 10.1136/hrt.60.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous balloon dilatation of the mitral valve: an analysis of echocardiographic variables related to outcome and the mechanism of dilatation.

Abstract: Percutaneous balloon dilatation of the mitral valve is a promising new approach to the management of rheumatic mitral stenosis.1w But at this early stage little is known about the criteria for patient selection or the mechanism by which balloon dilatation increases mitral valve area. Previous experience with closed surgical commissurotomy suggests that mitral valve pliability and the degree of leaflet thickening have an important effect on subsequent outcome.'"" Because cross sectional echocardiography shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
483
4
35

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,069 publications
(536 citation statements)
references
References 16 publications
14
483
4
35
Order By: Relevance
“…The importance of the Wilkins et al 10 echocardiographic scores is demonstrated in the results obtained in percutaneous mitral balloon valvuloplasty 30 . Because our percutaneous mitral balloon valvuloplasty postsurgical mitral commissurotomy group had higher echo scores than the primary percutaneous mitral balloon valvuloplasty group, 7.7±1.5 versus 7.2±1.4 points (p=0.0158) and a tendency toward slightly better results in the primary percutaneous mitral balloon valvuloplasty group, we redivided the total 459 procedures into a patient group with echo scores ≤8 and a patient group with echo scores >8 to better study the influence of echocardiographic scores on the obtained results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the Wilkins et al 10 echocardiographic scores is demonstrated in the results obtained in percutaneous mitral balloon valvuloplasty 30 . Because our percutaneous mitral balloon valvuloplasty postsurgical mitral commissurotomy group had higher echo scores than the primary percutaneous mitral balloon valvuloplasty group, 7.7±1.5 versus 7.2±1.4 points (p=0.0158) and a tendency toward slightly better results in the primary percutaneous mitral balloon valvuloplasty group, we redivided the total 459 procedures into a patient group with echo scores ≤8 and a patient group with echo scores >8 to better study the influence of echocardiographic scores on the obtained results.…”
Section: Discussionmentioning
confidence: 99%
“…The following parameters were studied: age, sex, rhythm, preprocedure NYHA functional class, mitral valve, echo score 10 , preprocedure echo mitral valve area, pre-and postballoon valvuloplasty mean pulmonary artery pressure, pre-and postprocedure mean mitral gradient, pre-and postprocedure hemodynamic measured mitral valve area, and pre-and postprocedure mitral regurgitation. The data obtained in the 2 groups were compared.…”
Section: Methodsmentioning
confidence: 99%
“…The morphologic features of the mitral valve were categorized using the Wilkins echo score 13 and the total echocardiographic score was obtained by adding the scores for leaflet mobility, thickness, calcification, and subvalvular lesions. MVA was measured by direct planimetry in parasternal short-axis view, and continuous wave Doppler was used to calculate peak pressure gradient of tricuspid regurgitation.…”
Section: Echocardiographic Evaluationmentioning
confidence: 99%
“…(5) Rheumatic disease, in turn, is considered the most important causal determinant of valve diseases, as the scar from the inflammatory process that affects the follow-up of the heart during episodes of rheumatic fever causes deformation of the heart valves. (6) The cardiovascular changes associated with pregnancy and the postpartum period can contribute to the clinical worsening of these patients' condition and, often, to the initial diagnosis of a valve disease. (7) In this period, the circulating blood volume increases by about 30 to 50%.…”
Section: Introductionmentioning
confidence: 99%